2018
DOI: 10.1128/jcm.01785-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Serological Methods and Two Reverse Transcription-PCR Assays for Diagnosis and Surveillance of Zika Virus Infection

Abstract: 24Zika virus (ZIKV) is a mosquito-borne flavivirus that is responsible for recent explosive 25 epidemics in the Americas. Notably, ZIKV infection during pregnancy has been found to cause 26 congenital birth defects, including microcephaly, and ZIKV has been associated with Guillain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 34 publications
(50 reference statements)
5
66
0
3
Order By: Relevance
“…2B and 3B). This was in agreement with a recent study of a blockade-of-binding ZIKV NS1 ELISA (25), in which the detection rate increased (77.4% to 98.3%) from early convalescent to late convalescent phases for the pZIKV panel and remained high (92.3% to 94.4%) for the ZIKVwprDENV panel. Our ZIKV NS1 IgG ELISA had an overall sensitivity of 100%, which is higher or compatible with those reported recently (79% to 100%) using the Euroimmun ZIKV NS1 IgG ELISA kit (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2B and 3B). This was in agreement with a recent study of a blockade-of-binding ZIKV NS1 ELISA (25), in which the detection rate increased (77.4% to 98.3%) from early convalescent to late convalescent phases for the pZIKV panel and remained high (92.3% to 94.4%) for the ZIKVwprDENV panel. Our ZIKV NS1 IgG ELISA had an overall sensitivity of 100%, which is higher or compatible with those reported recently (79% to 100%) using the Euroimmun ZIKV NS1 IgG ELISA kit (41)(42)(43)(44).…”
Section: Discussionsupporting
confidence: 93%
“…A study of human MAbs against nonstructural protein 1 (NS1) revealed that most anti-NS1 MAbs derived from patients with pZIKV infection were specific to ZIKV, and Ͼ50% of those from patients with ZIKVwprDENV infection reacted to DENV (21); other studies using ZIKV-specific NS1 MAbs in blockade-of-binding enzyme-linked immunosorbent assays (ELISAs) showed that ZIKV NS1 protein in serodiagnosis can distinguish ZIKV and DENV (24,25). We reported previously that the combination of ZIKV and DENV1 NS1 ELISAs distinguishes pZIKV, primary DENV1 (pDENV1), secondary DENV (sDENV,) and ZIKVwprDENV infections (26).…”
mentioning
confidence: 99%
“…In particular, the assay has a 95% sensitivity and a specificity against DENV of 89% in patient samples >20 d after the onset of symptoms compared with RT-PCR results. In late convalescent samples (e.g., >7 mo postillness as in the samples used in the present study), the assay's sensitivity and specificity rose to 96 and 92%, respectively, in a validation study performed in Nicaragua (24,25). This study aimed to (i) determine the seroprevalence of anti-ZIKV antibodies after the first Zika epidemic in Managua, (ii) describe the age patterns of ZIKV infection, (iii) identify potential risk factors that correlate with ZIKV infection, and (iv) characterize the neighborhood-specific spatial distribution of ZIKV seroprevalence within our study populations.…”
mentioning
confidence: 57%
“…Our study used a new competition ELISA to detect total anti-ZIKV NS1 antibodies. The assay distinguishes between ZIKV and DENV infections with high sensitivity and specificity for up to several years postinfection and has been validated in six countries (including Nicaragua) (24,25). In particular, the assay has a 95% sensitivity and a specificity against DENV of 89% in patient samples >20 d after the onset of symptoms compared with RT-PCR results.…”
mentioning
confidence: 99%
“…Laboratory confirmation of a diagnosis for patient treatment must have sufficient clinical sensitivity and specificity to be useful, the criteria for which may be different than analytical sensitivity and specificity criteria specified by assays for use in vaccine trials. [38][39][40][41][42][43][44][45] Very few tests have gained Emergency Use Authorization (EUA) from the FDA. There are 2 MERS-CoV diagnostic tests, both molecular-based viral RNA detection, which received EUA in 2013 in response to the recognition of the significant potential for a future public health emergency.…”
Section: Diagnostics For Emerging Infectious Diseasesmentioning
confidence: 99%